Varumärkets ensamrätt i konflikt med yttrandefriheten - Karlzén,Frida (2026)
This thesis examines the conflict between the exclusive rights conferred by trade-mark law and the right to freedom of expression within the framework of EU law. The analysis focuses in particular on how the concept of due cause should be in-terpreted when a well known trademark is used by a third party for the purpose of conveying political and/or parodic messages. The background to the thesis is the still pending case C 298/23, IKEA v. Vlaams Belang, in which the Belgian polit-ical party Vlaams Belang used IKEA’s signs in connection with a political cam-paign. IKEA argued that this constituted trademark infringement, whereas Vlaams Belang maintained that the use was protected by the right to freedom of expression. The aim of the thesis is to analyse how Article 9(2)(c) of the Trade Mark Directive and Article 10(2)(c) of the Trade Mark Regulation ought to be interpreted when freedom of expression is invoked as due cause, and how the balancing should be conducted between the third party’s freedom of expression and the trademark proprietor’s right to property in such circumstances. The principal analysis exam-ines the fundamental rights that come into conflict, as well as the relevant aspects of EU trademark law. This is undertaken through consideration of case law, legal literature, and other EU law sources. The thesis demonstrates that the concept of due cause should function as a mechanism for incorporating freedom of expression into trademark law, but that further guidance from the Court of Justice is required to clarify which factors should be accorded weight in the assessment. In the absence of such guidance, the thesis concludes that the strong protection afforded to political expression should be given particular significance in the balancing between freedom of expression and the right to property. Against this background, the prevailing considerations indicate that the use at issue in the dispute between IKEA and Vlaams Belang ought to be regarded as permissible, and that this in general should be the case with political and/or parodical use of well-known trademarks.
Keywords: EU-rätt; Immaterialrätt; Varumärkesrätt; Yttrandefrihet